An introduction to retroviruses: replication strategy and genetics - Stoye, Jonathan (Henry Stewart Talks, 2007)
Retroviruses, Life cycle, Classification, Simple and complex retroviruses, Endogenous retroviruses, Retroviruses and cancer
Reviewed at 2017/03/08